OPTIMIZATION OF A NOVEL KINETIC-ASSISTED INFUNDATION FOR RICH-EGCG AND POLYPHENOLS OF WHITE TEA (CAMELLIA SINENSIS) USING CENTRAL COMPOSITE DESIGN - Shiyan, Shaum; Hertiani, Triana; Martien, Ronny; Nugroho, Akhmad Kharis (International Journal of Applied Pharmaceutics, 2018)
Objective: This research aimed to find modeling and optimization of a novel kinetic-assisted infundation for rich-epigallocatechin gallate (EGCG) and polyphenols extraction from white tea leaf (Camellia sinensis L.). Methods: The optimal conditions for the best extraction of kinetic-assisted infundation were determined using central composite design. The content of EGCG, catechin, gallic acid, caffeine, theobromine, and theophylline was quantified using high-performance liquid chromatography with ultraviolet detection (HPLC/UV-detection). The total polyphenolic content (TPC) and total flavonoid content (TFC) was measured using the spectrophotometric method. The semi-purified extract was characterized by HPLC, fourier transform infrared spectrophotometry-universal attenuated total reflectance (FTIR-UATR), and powder-X ray diffraction (P-XRD). The extraction mechanism of target compounds was analyzed using scanning electron microscopy (SEM) qualitatively. Results: The optimum process for the rich-EGCG and polyphenolic extraction using kinetic-assisted infundation was the concentration of simplicia 14.75 %, the stir rate 440 rpm, and extraction time 12.31 min. The yield of extracts, TPC, TFC, EGCG, caffeine, gallic acid, and theobromine contents in the optimal extraction process were 9.34 %, 70.97 %, 13.95 %, 29.02 %, 11.95 %, 1.33 %, and 0.33 %, respectively. Conclusion: The kinetic-assisted infundation method proved to be easy to apply with good results as an alternative technique for extracting polyphenolic compounds and rich-EGCG from white tea leaves.